Time Adjustment of Hydrocortisone Doses During Shift Work in Patients with Adrenal Insufficiency - Kienitz, Tina; Strasburger, Christian; Elbelt, Ulf; Lang, Katharina; Mai, Knut; Bobbert, Thomas; Quinkler, Marcus (Hormone and Metabolic Research, 2025)
Shift work causes a disruption between the circadian system and the external light-dark cycle, but also a misalignment between various levels of the circadian system. There is no information on patients with adrenal insufficiency (AI) who are working shifts. The objective of the study was to analyze the hormone replacement therapy with hydrocortisone (HC) and the adaptation scheme in patients with AI on shifts. Patients working on shifts (n=15) from two German endocrine centers received a questionnaire regarding their therapy scheme, dose adaptations, working shifts, dose adaptations during working shifts, and occurrence of adrenal crisis. We observed that 20% of patients stated that they experience difficulties taking glucocorticoid replacement on time, 40% of patients reported these difficulties to occur only occasionally. Consequently, nearly half of the patients had forgotten to take their replacement therapy at some point. More than 50% of patients reported an adrenal crisis during the last two years. The timely adaptation of HC or of modified-release HC during shifts was very inhomogeneous. In conclusion, the adaptation schemes for HC dosing during shift work are currently not evidence-based but opinion-driven. Our findings highlight the need for further investigations of shift workers with AI.
Keywords: hydrocortisone; Addison’s disease; circadian rhythm; secondary adrenal insufficiency; modified-release hydrocortisone